مساهمة تثمين إدارة النفايات في تجسيد أبعاد التنمية المستدامة في الجزائر عرض تجارب محلية - لسود, راضية (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى تسليط الضوء على مساهمة تثمين ادارة النفايات في تجسيد أبعاد التنمية المستدامة، و ذلك من خلال تقديم رؤية شاملة حول مفهوم إعادة تدوير النفايات و مدى مساهمتها في تحقيق التنمية المستدامة من خلال عرض بعض التجارب لمؤسسات جزائرية تمارس إعادة تدوير النفايات. توصلنا من خلال هذه الدراسة إلى جملة من النتائج أهمها يسمح توجه المؤسسات نحو اقتصاد الدائري و بالضبط نحو إعادة تدوير النفايات بتحقيق أبعاد التنمية المستدامة بشكل فعال. This study aimed to shed light on the contribution of valuing waste management to embodying the dimensions of sustainable development, by presenting a comprehensive view on the concept of waste recycling and its contribution to achieving sustainable development by presenting some experiences of Algerian institutions that practice waste recycling. Through this study, we have reached a set of results, the most important of which is that the institutions' orientation towards a circular economy and precisely towards recycling of waste allows them to effectively achieve the dimensions of sustainable development.
Contribution of waste management valuation to embodying the dimensions of sustainable development in Algeria Show local experiences
مقال
Keywords: إعادة تدوير ; النفايات ; التنمية المستدامة ; أبعاد التنمية المستدامة ; الجزائر